Role of CD20+T lymphocytes in the pathogenesis of multiple sclerosis - N. S. Glebezdina (Медицинская иммунология, 2024)
CD3+CD20+T lymphocytes are a population of T cells that, along with standard T cell markers, express the atypical membrane molecule CD20 (a traditional B cell marker). These cells were identified not so long ago and are currently being actively studied. Normally, they constitute up to 3-5% of the CD3+T cell compartment in human peripheral blood, and are also found in primary and secondary lymphoid organs, cerebrospinal fluid, brain tissue and liver. In healthy individuals, CD3+CD20+T cells are heterogeneous and contain a lower proportion of CD4+ cells, but produce higher levels of GM-CSF, IFNγ, IL-17, TNFα, IL-4, IL-10, adhesion molecules and chemokine receptors than CD3+CD20-T cells, indicating a highly activated proinflammatory phenotype with properties potentially promoting their pathogenic infiltration into the CNS. Recent studies have established the pathogenic behavior of CD3+CD20+T cells in a wide range of diseases, including hematological and non-hematological CD20+T cell malignancies and HIV, as well as autoimmune pathologies, in particular multiple sclerosis, a disabling inflammatory neurodegenerative disease that is accompanied by damage to the myelin sheath nerve fibers. CD20 positive T cells are detected in patients with multiple sclerosis in the peripheral blood, cerebrospinal fluid (occur at a frequency similar to that of B cells and show a correlation with disease severity) and white matter of the brain. CD20 positive T lymphocytes in the peripheral blood of patients with multiple sclerosis have been shown to produce high levels of IFNγ and IL-17А, which are two proinflammatory cytokines involved in the pathogenesis of this disease. It is possible that CD20+T cells represent a separate subpopulation of Th17 cells, the so-called Th1-polarized Th17, which are the product of redifferentiation of Th17 cells into Th1 and combine the phenotypic characteristics of both populations. And the expression of CD20 T cells may be a valuable marker that determines the target subpopulation of such pathogenic T cells, as well as serve as a target for therapy of autoimmune diseases.